1982
DOI: 10.4095/109261
|View full text |Cite
|
Sign up to set email alerts
|

Systematic descriptions, paleoecology and correlations of the late paleozoic subfamily spiriferellinae (brachiopoda) from the Yukon Territory and the canadian arctic archipelago

Abstract: Sixteen species of the brachiopod subfamily Spiriferellinae Waterhouse are described from the Upper Carboniferous and Early to Middle Permian beds of the Yukon Territory and the Canadian Arctic Archipelago. New taxa are Spiriferella primaeva n. sp., S. yukonensis n. sp., S. leviplica n. sp., Eridmatus petita n. sp., Elivina cordiformis n. sp., Plicatospiriferella canadensis n. gen., n. sp., and Alispiriferella ordinaria (Einor) n. gen. The remaining species are all shared with the Soviet Union and/or Arctic is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Previous studies have shown that spiriferellid taxa generally have posterolaterally tapering spiralia similar to those in all other spiriferide brachiopods (Fig. ; see also Nelson & Johnson ; Cooper & Grant ; Waterhouse & Waddington ; Lee et al . ).…”
Section: Methodsmentioning
confidence: 70%
“…Previous studies have shown that spiriferellid taxa generally have posterolaterally tapering spiralia similar to those in all other spiriferide brachiopods (Fig. ; see also Nelson & Johnson ; Cooper & Grant ; Waterhouse & Waddington ; Lee et al . ).…”
Section: Methodsmentioning
confidence: 70%
“…Spirif~r~lla orditzuricr in the northern Yukon extends rrom the middle of the Jungle Creek Formation to the middle of the Tahkandit Formation, an interval probably repre~enting Leonardian. Waterhouse and Waddington (1982). however.…”
Section: Analysis Of Brachiopod Faunamentioning
confidence: 96%
“…Yr~kovlevia transversrr appears to he confined ro the Jungle Creek Fwrmation of that area, the so-called "Middle Recesqiv~ unit" of Nelson (1961'1 and Nelson and Johnson (19hXI. This unit was dated by these writers to be Wolfcampian and early'? Leoaardian, the same time span later assigned to it by Bamber and Waterhouse, There is considerable disagreement between Nelson and Johnson (196%) and Waterhouse and Waddington (1982) about the stratigraphic positions o f the various species of Spiriferell~. The first authors conside~d most of them to he long ranging, the latter short ranging.…”
Section: Analysis Of Brachiopod Faunamentioning
confidence: 99%
“…Genus Alispiriferella Waterhouse and Waddington, 1982 Alispiriferella neimongolensis Wang and Zhang, 2003 Fig. 6: 3 2003 Alispiriferella neimongolensis Wang and Zhang,p.…”
Section: Fig 5:mentioning
confidence: 98%